Proteomics and antioxidant enzymes reveal different mechanisms of toxicity induced by ionic and nanoparticulate silver in bacteria - Barros, Diana (2019)
The increased use of silver nanoparticles (AgNPs) raises concerns about their impacts on aquatic ecosystems. The impacts of Ag+ and AgNPs were assessed on proteomic and antioxidant enzymatic responses of Pseudomonas sp. M1. The effects of Ag+ on bacterial growth were stronger than those of AgNPs (EC20 = 107.1 μg L−1 for Ag+; EC20 = 307.2 μg L−1 for AgNPs), indicating the lower toxicity of the latter. At EC20, the activities of antioxidant enzymes increased more under exposure to Ag+ than to AgNPs, particularly for superoxide dismutase and glutathione peroxidase (stimulation of 667% and 433%, respectively). A total of 166 proteins were identified by SWATH-MS; among these, only 59 had their content significantly altered by one or both forms of silver. Exposure to AgNPs resulted in an increase of about 54% of these proteins, whereas 54% decreased under exposure to Ag+. Gene Ontology enrichment analysis revealed that protein folding and transmembrane transport were the most relevant processes affected by Ag+ exposure, whereas AgNPs mostly affected translation. Also, results suggest that each form of silver induced different adaptive responses. Furthermore, the low levels of Ag+ released from AgNPs (<0.1%) support a minor role of dissolved silver in AgNP toxicity to Pseudomonas sp. M1